Analysis of Interpersonal Communication Ethics of UINSU FIS Students Against Lecturers Through the Whatsapp Application - Dinda R. A. Hasibuan; Nurmala Lubis; Rahma S. Asdi; Zaki Fahri; Kartini Kartini (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2022)
This study discusses the ethics of communication between students of the Faculty of Social Sciences, UIN SU and lecturers through the WhatsApp application. This study aims to determine the ethics of interpersonal communication between students of the Faculty of Social Sciences, UIN SU and lecturers through the WhatsApp application and the effect of the age of the lecturer on the way students communicate with their lecturers. This study uses a qualitative descriptive method that describes the ethics of interpersonal communication between the students of the Faculty of Social Sciences, UIN SU towards lecturers using the WhatsApp application. The results of this study indicate that the ethics of interpersonal communication between students of the Faculty of Social Sciences UIN SU to lecturers through the WhatsApp application are mostly considered ethical and polite because they follow good and ethical speech rules. Students are able to place themselves as students who are dealing with lecturers as people who deserve to be respected and appreciated. In addition, the lecturer's age factor also affects the way students communicate with lecturers.